Menstrual Hygiene Management and its Association with Socio-economic Inequalities: A Cross-Sectional Study at Two Tertiary Care Hospitals of Rawalpindi - Suhail, Iman; Sajid, Ifrah; Zulfiqar, Shaista; Akhtar, Aisha; Suhail, Mishal (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the degree of awareness and affordability of menstrual products among women of various socioeconomic classes.Study Design: Cross-sectional study.Place and Duration of Study:  Obstetrics and Gynecology Outpatient Department, Fauji Foundation Hospital, Rawalpindi and Combined Military Hospital, Rawalpindi Pakistan, from Jan to Jul 2023.Methodology: A total of 434 females aged 15-49 years were included, out of which 217 were from Fauji Foundation Hospital, Rawalpindi and 217 from Combined Military Hospital, Rawalpindi. A validated, structured questionnaire was given to all respondents. to compare associations of socio-economic status with knowledge and affordability of menstrual products.Results: Data showed a positive association between mothers’ level of education and their daughters’ early knowledge of menstruation. The source of this knowledge predominantly is mother. When use of product of choice, reasons for not using a tampon/menstrual cup, washing genitalia after each toilet visit, bathing and reasons for not bathing during menses, pain relieve during menses and indulgence in going out during menses were compared in respondents with higher education versus lower education, there was significant association seen in the higher educational group (p